(untitled) (Research, Society and Development, 2022)
The existing microbiota in humans is the result of years of evolution of a symbiotic relationship. this relationship has brought us numerous benefits, including protection against pathogens, maintenance of intestinal barrier integrity, nutrient and drug metabolism, vitamin synthesis (k and b12), and temperature production and nutrient availability. microorganisms are in large numbers in the human organism, reaching approximately ten times more microbial cells than cells. The gut microbiota plays an important role in the normal function of the gut and maintenance of the host’s health. influencing not only gastrointestinal diseases, but the healthy and microbiologically balanced intestinal microbiota results in a normal performance of the host’s physiological functions, which will ensure an Microbiota improvement in the quality of life.